Nilai-Nilai Moral Terkandung dalam Tradisi Arakan Sahur di Kabupaten Tanjung Jabung Barat - Hariandi, Ahmad; Sari, Chika Orsalia Yovita; Zahara, Denisya; Hapsari, Hasta Purwindah; Mubarokah, Lailatul Badriatul (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2023)
The people of Kuala Tungkal are characterized by this culture in their own unique way. The Arakan Sahur tradition is one that originates from Kuala Tungkal. In this tradition, members of the public play Malay musical instruments such as drums, kulintang, tambourines and bells to prepare food for the procession, which have been passed down from generation to generation. Today, this tradition is part of the annual calendar of West Tanjung Jabung Regency. As a result, researchers are interested in lifting this tradition to investigate its moral principles. An emic approach to qualitative research is used in this study. The findings of this study indicate that the Arakan Sahur tradition which has existed since the time of our ancestors and is still practiced today contains moral principles. Religious Values, Social Values, Cultural Values, Educational Values, and Cultural Values are the four moral values. This tradition must be protected and strengthened by continuing to carry out the Sahur Arakan tradition consistently during the holy month of Ramadan as a sign of Kuala Tungkal City residents and a form of appreciation for being given the opportunity to feel the atmosphere of Kuala Tungkal City. this fasting month. Masyarakat Kuala Tungkal dicirikan oleh budaya ini dengan caranya sendiri yang unik. Tradisi Sahur Arakan adalah salah satu yang berasal dari Kuala Tungkal. Dalam tradisi ini, anggota masyarakat memainkan alat musik Melayu seperti gendang, kulintang, rebana, dan genta untuk menyiapkan makanan arakan telah diwariskan secara turun-temurun. Hari ini, tradisi ini menjadi bagian dari kalender tahunan Kabupaten Tanjung Jabung Barat. Akibatnya, para peneliti tertarik untuk mengangkat tradisi ini untuk menyelidiki prinsip-prinsip moralnya. Pendekatan emic untuk penelitian kualitatif digunakan dalam penelitian ini. Temuan penelitian ini menunjukkan bahwa tradisi Sahur Arakan yang telah ada sejak zaman nenek moyang dan masih dipraktikkan hingga saat ini mengandung prinsip-prinsip moral. Nilai Religius, Nilai Sosial, Nilai Budaya, Nilai Pendidikan, dan Nilai Budaya adalah empat nilai moral. Tradisi ini harus dilindungi dan dikukuhkan dengan terus melaksanakan tradisi Sahur Arakan secara konsisten selama bulan suci Ramadhan sebagai tanda warga Kota Kuala Tungkal dan bentuk penghargaan karena masih diberi kesempatan untuk merasakan suasana Kota Kuala Tungkal. bulan puasa ini.